Small molecule inhibitors of the annexin A2 heterotetramer prevent human papillomavirus type 16 infection. (23rd February 2015) - Woodham, Andrew W.; Taylor, Julia R.; Jimenez, Andrew I.; Skeate, Joseph G.; Schmidt, Thomas; Brand, Heike E.; Da Silva, Diane M.; Kast, W. Martin
Abstract: Objectives: High-risk human papillomavirus (HPV) infection leads to the development of several human cancers that cause significant morbidity and mortality worldwide. HPV type 16 (HPV16) is the most common of the cancer-causing genotypes and gains entry to the basal cells of the epithelium through a non-canonical endocytic pathway that involves the annexin A2/S100A10 heterotetramer (A2t). A2t is composed of two annexin A2 monomers bound to an S100A10 dimer and this interaction is a potential target to block HPV16 infection. Here, recently identified small molecule inhibitors of A2t (A2ti) were investigated for their ability to prevent HPV16 infection in vitro . Methods: A2ti were added to HeLa cells in increasing concentrations prior to the addition of HPV16. Cytotoxicity was evaluated via trypan blue exclusion. HPV16 pseudovirion infection and fluorescently labelled HPV16 capsid internalization was measured with flow cytometry. Results: A2ti blocked HPV16 infection by 100% without substantial cellular toxicity or reduction in cell growth. Furthermore, A2ti blocked HPV16 entry into epithelial cells by 65%, indicating that the observed inhibition of HPV16 infection is in part due to a block in entry and that non-infectious entry may occur in the absence of A2t binding. Conclusions: These results demonstrate that targeting A2t may be an effective strategy to prevent HPV16 infection.